2021
DOI: 10.1001/jamacardio.2020.4414
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Trans–Right Atrial Access to the Left Ventricle for Catheter Ablation of Ventricular Tachycardia in Patients With Mechanical Aortic and Mitral Valves

Abstract: IMPORTANCEIn patients with mechanical valves in the aortic and mitral positions, percutaneous access to the left ventricle (LV) via a transfemoral approach for catheter ablation of ventricular tachycardia (VT) has been considered infeasible.OBJECTIVE To describe the outcomes of a novel percutaneous trans-right atrial (RA) access to the LV via a femoral venous approach for catheter ablation of VT in patients with mechanical aortic and mitral valves. DESIGN, SETTING, AND PARTICIPANTSThis observational study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Finally, while in the original published series of RA-to-LV access 2 of the 4 patients developed sustained ventricular arrhythmias requiring cardioversion during use of the RF wire, 1 in our case only short runs of nonsustained VT were induced with RF, which we believe was because we chose to use shorter 1-second bursts rather than 4- to 5-second bursts as previously described. Furthermore, after balloon dilation, the sheath was successfully advanced using a technique known as balloon-assisted tracking.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Finally, while in the original published series of RA-to-LV access 2 of the 4 patients developed sustained ventricular arrhythmias requiring cardioversion during use of the RF wire, 1 in our case only short runs of nonsustained VT were induced with RF, which we believe was because we chose to use shorter 1-second bursts rather than 4- to 5-second bursts as previously described. Furthermore, after balloon dilation, the sheath was successfully advanced using a technique known as balloon-assisted tracking.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, stereotactic radioablation 5 was considered; however, without prior electroanatomic mapping or contrast imaging to guide dose planning, it was felt to have a lower chance of success. Thus, a direct RA-to-LV approach 1 was felt to be the optimal approach. Furthermore, in case of difficulty with sheath contact or stability in this region, we discussed attempting puncture from just inside the ostium of the coronary sinus, as has been anecdotally reported; however, this was ultimately not required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, options would include epicardial approach, 29 transventricular septal puncture, 30 transcoronary venous approach, 31 transapical approach, 32 or trans-right atrial to the LV approach. 33 Percutaneous epicardial access can be challenging in patients with prior cardiac surgery. A previous study reported that prior cardiac surgery precludes LV access in most patients with only 20% success rate.…”
Section: Left Ventricular Accessmentioning
confidence: 99%
“…Several operators have reported on the application of non-conventional techniques for VT ablation, including transventricular septal puncture, transmechanical valve, transcoronary venous, and transapical approaches. 1 5 Promising alternatives to radiofrequency ablation include percutaneous or surgical sympathetic neuromodulation, alcohol ablation from the coronary arterial or venous system, direct current or pulsed-field electroporation, and noninvasive stereotactic radioablation therapy (SBRT) in critically ill patients. 6 9 We herein describe the effect of SBRT as a bailout therapy on the management of a challenging VT case with two mechanical valve prostheses in aortic and mitral positions.…”
Section: Introductionmentioning
confidence: 99%